Hatching success and growth of Snakehead (Channa lucius Cuvier, 1831) larvae and fry at different pH levels - Ly Tien Hai; Huang Cheng-Ting; Lee Po-Tsang; Vo Van Thanh; Diep Doan Xuan (Aquatic Living Resources, 2024)
Snakehead (Channa lucius Cuvier, 1831) is a species of potential aquaculture interest in the Mekong Delta, Vietnam. However, their optimum environmental conditions have yet to be determined. This study aims to study the hatching success and larval and fry growth of C. lucius at six pH levels (5.5, 6.0, 6.5, 7.0, 7.5, and 8.0). Two consecutive experiments were conducted. Experiment 1 focused on incubating eggs and nursing the yolk sac larvae, and was carried out in aquariums. The monitoring included incubation time (IT), hatching rate (HR), and deformation rate of the newly hatched larvae (DR). Larvae were also collected daily during nursing for growth determination. In Experiment 2, four-day-old fry after hatching from experiment 1 were reared in plastic tanks with live feeds for 30 days. Growth was checked every ten days, while survival rate (SR) and coefficient of variation (CV) were determined at the end of the experiment. pH 5.5–8.0 was favorable for incubation, larvae, and fry, as assessed through good indicators of IT, HR, DR, and larval length and weight growths, as well as length and weight growths, SR, and CV of fry. Furthermore, the lowest DR (0.33%) was at pH 5.5, while except for pH 7.0, the shortest IT (41.1 h) significantly differed from that at higher pH levels (p < 0.05), and the highest larval growth parameters were at pH 5.5–6.0; meanwhile, pH 5.5–6.5 supported a better life for fry, as showed by the significantly higher growth parameters (p < 0.05) and SR and CV improvements in fry after 30 rearing days. Overall, pH 5.5–8.0 was suitable for the early stages of C. lucius, in which pH 5.5–6.0 was better for incubation and larval growth and pH 5.5–6.5 was better for fry development.